Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Joint Position Statement on the Linguistic Variable - Regroupement des Entités de planification des services de santé en français de l'Ontario (2013)

Better data for better planning: The challenge of evidence-based data for sound planning of French-Language health services in Ontario - Réseau des services de santé en français de l’Est de l’Ontario (The challenge of evidence-based data for sound planning of French-Language health services in Ontario, 2013)

Des données pour mieux planifier: Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario - Réseau des services de santé en français de l’Est de l’Ontario (Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario, 2013)

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales